Understanding the Effect of Electron Irradiation on WS2 Nanotube Devices to Improve Prototyping Routines - Kovařík, Martin; Citterberg, Daniel; Paiva de Araújo, Estácio; Šikola, Tomáš; Kolíbal, Miroslav (ACS applied electronic materials, 2024)
To satisfy the needs of the current technological world that demands high performance and efficiency, a deep understanding of the whole fabrication process of electronic devices based on low-dimensional materials is necessary for rapid prototyping of devices. The fabrication processes of such nanoscale devices often include exposure to an electron beam. A field effect transistor (FET) is a core device in current computation technology, and FET configuration is also commonly used for extraction of electronic properties of low-dimensional materials. In this experimental study, we analyze the effect of electron beam exposure on electrical properties of individual WS2 nanotubes in the FET configuration by in-operando transport measurements inside a scanning electron microscope. Upon exposure to the electron beam, we observed a significant change in the resistance of individual substrate-supported nanotubes (by a factor of 2 to 14) that was generally irreversible. The resistance of each nanotube did not return to its original state even after keeping it under ambient conditions for hours to days. Furthermore, we employed Kelvin probe force microscopy to monitor surface potential and identified that substrate charging is the primary cause of changes in nanotubes’ resistance. Hence, extra care should be taken when analyzing nanostructures in contact with insulating oxides that are subject to electron exposure during or after fabrication.